Endangered Voices: A Sociological and Anthropological Review of the Kusunda Language and Culture - Pokharel , Saroj; Adhikari , Bhawani Shankar; Dhakal, Krishna Prasad; Dahal, Shree Ram (Journal of Research in Education, 2025)
This systematic review aims to disentangle the multifactorial collapse of the Kusunda Language and Culture of Nepal’s Kusunda Indigenous Community to ascertain possible shifts that may sustain revitalization efforts. Systematic review of peer-reviewed articles, ethnography, history, and policies available from JSTOR, Google Scholar, and national archives. Articles were filtered and selected based on the relevance to Kusunda, as it applies to linguistics, culture, socioeconomics, and initiatives to preserve fading languages. The Kusunda language is classified as a linguistic isolate and is nearly extinct, with a total of 160 community members and 1 fluent speaker left. Language shifts to Nepali occurs as a result of forced sedentarization, labor migration, exogamous marriage, and educational exclusion. The systematic erosion of Kusauda culture is a result of the animist belief systems, deforestation and agricultural expansion, and social cohesion which stem from the 1854 Muluki Ain that codified caste-based discrimination. With the exception of Women who have assumed the role of inter-generational activities, no single member of the community has fully revitalized the culture, although some have attempted to do so, albeit with insufficient resources. It is essential that intersectional measures to preservation are integrated including the linguistic and the structural. Preservation policies should include integrated economic interventions related to food security, health, and housing, as well as the provision of tools for digital documentation, policies that support community-based bilingual education (and Kusunda as a medium of teaching), and subsidized bilingual education for children. In the preservation of cultural practices, the critical role of women must be recognized. Without this type of coordinated action that encompasses multiple sectors, including government, civil society, and academia, the preservation of the Kusunda language and its knowledge systems is doomed.